Hans and Sophie Scholl : German resisters of the White Rose - Axelrod, Toby (Holocaust biographies, 2001)
Historical account of the establishment of the secret opposition group known as the German Resisters of the White Rose and its founders, Hans and Sophie Scholl, who formed this group during World War II in opposition to Hitler and his fascist dictatorship.